Predictors of high hospital admission and criminal reoffending in adults experiencing homelessness: a retrospective cohort study - Mitchell, Rebecca; Burns, Nicholas; Glozier, Nicholas; Nielssen, Olav (International Journal of Population Data Science, 2024)
Objectives To examine the costs and predictors of high hospital use and criminal reoffending in adults experiencing homelessness. Approach Retrospective cohort study of 2,140 adults who attended homeless hostel clinics in New South Wales, Australia using linked clinic, health, criminal offence, and mortality data from 1 July 2008 to 30 June 2021. Multivariable logistic regression examined predictors of high all-cause hospital use (≥4 emergency department presentations in 12 months) and predictors of recidivism. Results There were 27,466 hospitalisations at a total cost of AUD548.2 million. Twenty-seven percent of the cohort had high hospital use. Factors associated with high use were age ≥45 years, female (AOR: 1.52; 95%CI 1.05-2.22), presence of a mental disorder, substance use disorder (AOR: 1.36; 95%CI: 1.03-1.82), or being homeless for >1 year (AOR: 1.31; 95%CI: 1.06-1.62). There were 1,646 (76.9%) adults who had contact with the criminal justice system. Most (75.3%) reoffended within 24 months after index offence, and reoffenders were more likely to be younger, have a personality disorder (AOR: 1.31; 95% CI: 1.04-1.67), substance use disorder (AOR: 1.60; 95%CI 1.14-2.23), and had a previous charge dismissed on mental health grounds (AOR: 1.79; 95% CI: 1.31-2.46). Reoffenders more likely to have a principal theft-related offence (AOR: 1.85; 95%CI: 1.29-2.66). Total court finalisation costs were AUD11.3 million. Conclusions The high use of hospital and criminal justice services lends support to strategies to develop models of supported housing with a focus on integrated care, mental health support, improved referral pathways, and better coordination with community-based support agencies.